Anomaly and Stability in the Theory of Externalities - Sandmo, Agnar (Quarterly Journal of Economics, 1980)
Journal Article Anomaly and Stability in the Theory of Externalities Get access Agnar Sandmo Agnar Sandmo Norwegian School of Economics and Business Administration, Bergen Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 94, Issue 4, June 1980, Pages 799–807, https://doi.org/10.2307/1885670 Published: 01 June 1980